Income distribution in the United States - Miller, Herman P.; Social Science Research Council (U.S.) (Washington: U.S. Dept. of Commerce, Bureau of the Census, 1966)
The major finding of this book is that there was a reduction of inequality in the distribution of income between 1940 and 1950 but little, if any, change in this respect during the following decade.
osa;21/09/18
Loans
Keywords: Income distribution; Wages; United States